2021
DOI: 10.1177/0284185121997768
|View full text |Cite
|
Sign up to set email alerts
|

Shear-wave elastography for detection of placenta percreta: a case-controlled study

Abstract: Background Prenatal diagnosis of placenta percreta (PP) is important to be able to provide effective management and a multidisciplinary approach to minimize the complications. Purpose To evaluate the role of shear-wave elastography (SWE) in the prenatal diagnosis of PP. Material and Methods A total of 18 women with PP and 20 pregnant women with normal placenta in the second or third trimesters were included in this prospective study. SWE was used to determine the elasticities of the placenta (in the maternal e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 26 publications
0
6
0
Order By: Relevance
“…These comprised loss of the ‘clear zone’ (hypoechoic retroplacental zone), myometrial thinning, bladder‐wall interruption, presence of a placental bulge, uterovesical hypervascularity, placental lacunae and bridging vessels. None of the eight new signs identified in the present systematic review 14–28 reached a predefined consensus threshold as ultrasound findings that increase the probability of PAS at birth (Table 1). In addition, the panel was queried about second‐ or third‐trimester ultrasound findings that are not specific for PAS (i.e.…”
Section: Resultsmentioning
confidence: 92%
See 1 more Smart Citation
“…These comprised loss of the ‘clear zone’ (hypoechoic retroplacental zone), myometrial thinning, bladder‐wall interruption, presence of a placental bulge, uterovesical hypervascularity, placental lacunae and bridging vessels. None of the eight new signs identified in the present systematic review 14–28 reached a predefined consensus threshold as ultrasound findings that increase the probability of PAS at birth (Table 1). In addition, the panel was queried about second‐ or third‐trimester ultrasound findings that are not specific for PAS (i.e.…”
Section: Resultsmentioning
confidence: 92%
“…After exclusion of duplicates and two articles that were not available, 880 remained, of which a further 793 were excluded after screening the titles and abstracts, as the data they reported were not relevant. The remaining 87 studies were retrieved for full-text review, of which 72 were excluded after in-depth review, leaving 15 studies describing eight new ultrasound signs for the prenatal evaluation of PAS [14][15][16][17][18][19][20][21][22][23][24][25][26][27][28] . The process of selection of these articles is summarized in Figure S1, and the characteristics of the 15 studies identified by the systematic review are presented in Table S1.…”
Section: Literature Searchmentioning
confidence: 99%
“…11 Dokumaci and Uyanikoglu conducted the study in which the authors differentiated normally localized placenta and placenta previa on the basis of SWE of placenta. 12 Sugitani et al, conducted an ex-vivo assessment of placental elasticity and correlated with the histological changes observed in the placentas. 13 Simon et al, reported their SWE findings in the normal pregnancies and pre-eclamptic pregnancies.…”
Section: Discussionmentioning
confidence: 99%
“…SWI utilizes dynamic pressure to generate shear waves in parallel or vertical dimensions. Shear wave velocity can qualitatively and quantitatively estimate tissue elasticity [ 26 ]. The process can be summarized as follows: 1) The focused acoustic radiation force pushes the short-duration pulse; 2) the shear wave is generated within the organ of interest; 3) the speed of the shear wave propagation is measured away from the push position; and 4) the reported information can be averaged within an ROI (a point measurement) or as an image (shear wave elastography) and values are reported as shear wave velocity (Cs) or converted to the elastic modulus.…”
Section: Principles Of Ultrasound Elastography In Uterine Diseasesmentioning
confidence: 99%